Analysis of Physical and Electrical Properties of NiTe2 Single Crystal Grown via Molten Salt Flux Method - Je, Yeonjin; Kim, Eunjeong; Binh, Nguyen Vu; Kim, Hyeongtae; Cho, Su yeon; Lee, Do Hyeon; Kwon, Mi Ji; Choi, Moonhee; Lee, Jae Hyun; Nam, Woo Hyun; Lee, Younki; Cho, Jung Young; et al. (Electronic Materials Letters, 2023)
Since the emergence of layered two-dimensional materials, the development of methods for their large-scale synthesis has become crucial for integrating these materials into existing fabrication processes. In this study, we report the synthesis of a NiTe2 single crystal on the near-centimeter scale using the molten salt flux method (MSFM). The single-crystal nature of the synthesized NiTe2 sample was confirmed using X-ray diffraction analysis, while its chemical characteristics were analyzed using X-ray photoelectron spectroscopy, which confirmed Ni–Te chemical binding. The layered structure of the ingot was confirmed using Raman spectroscopy; two prominent signals were observed, at 84 and 138 cm−1, which were consistent with the in-plane vibrational mode, Eg, and out-of-plane vibrational mode, A1g. In addition, analyses performed on different flakes confirmed the structural uniformity of the single crystal, as only a small variation in the peak-to-peak position of the full width at half maximum was observed. Using Kelvin probe force microscopy, the electronic structure of the NiTe2 multilayered surface was investigated to determine its surface work function, which was found to be 4.4–4.8 eV. A back-gate field-effect transistor was fabricated using the single-crystal NiTe2 to evaluate its semimetallic characteristics; the transfer characteristic of the NiTe2 FET, determined by applying a back-gate bias, showed weak gate voltage dependence and linear I–V characteristics, in keeping with the linear ID-VD output characteristics. Therefore, the synthesis of NiTe2 via the MSFM should facilitate the integration of layered materials with existing fabrication processes for the mass production of electronic devices. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Dichalcogenides; Electronic.structure; Fabrication process; Flux methods; Molten salt; Molten salt flux; Salt flux; Secondary transition metal dichalcogenides; Secondary transitions; Vibrational modes; Electronic structure; Molten salt flux; NiTe2; Secondary transition metal dichalcogenides (TMDs); Single crystal